2013
DOI: 10.5194/bg-10-4751-2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, chemical properties and bioavailability of DOC in an early successional catchment

Abstract: Abstract. The dynamics of dissolved organic carbon (DOC) have been intensively studied in mature ecosystems, but little is known about DOC dynamics and the significance of DOC as a substrate for microbial activity in early-successional catchments. We determined the concentration, chemical composition, source, radiocarbon age, and bioavailability of DOC along the hydrological flow path from soil solution to a downstream pond in a recently constructed catchment (Chicken Creek Catchment, Germany). Soil solution, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…This indicates that the demand for P and N was much greater than for carbon, which matches the relatively high concentration of DOC in the flume water. Although the DOC in the water source of the flumes has been found to be highly recalcitrant (Risse‐Buhl et al ., ), algal exudates could have been a source of labile carbon for heterotrophic metabolism during the experiment (Besemer et al ., ). Similar observations on potential N‐ and P‐limitation have been made in a previous flume experiment conducted with ground water from the Chicken Creek catchment and natural sand‐bed sediments (Frossard et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the demand for P and N was much greater than for carbon, which matches the relatively high concentration of DOC in the flume water. Although the DOC in the water source of the flumes has been found to be highly recalcitrant (Risse‐Buhl et al ., ), algal exudates could have been a source of labile carbon for heterotrophic metabolism during the experiment (Besemer et al ., ). Similar observations on potential N‐ and P‐limitation have been made in a previous flume experiment conducted with ground water from the Chicken Creek catchment and natural sand‐bed sediments (Frossard et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…At the inflowing side of each flume, a honeycomb filter reduced any large flume irregularities resulting from the pump and generated low‐scale turbulence (Nowell & Jumars, ). An additional peristaltic pump (520‐SN; Watson Marlow, Falmouth) constantly supplied the flumes with well‐aerated ground water that was collected in the Chicken Creek catchment, a well‐characterised experimental site in Germany (51°36′N, 14°16′E, 171 m asl; Gerwin et al ., ; Risse‐Buhl et al ., ), and slightly amended with phosphorus to reach a final concentration of 2 μg L −1 (Table ). Initial measurements showed that under these standardised flow conditions, vertical water flux through gravel was higher than through the mixture or sand, which were characterised by similar fluxes (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…For this study, a time series with 6 yr of annual monitoring (2006)(2007)(2008)(2009)(2010)(2011) is available. The plant species were grouped by (i) lifespan according to Rothmaler (2000), but with only the two categories "annual" and "perennial"; (ii) life forms "grass-like", "herb" or "wood" according to Rothmaler (2000), species of the genus Rubus which in general form woody stems were thus labelled as "wood"; and (iii) affiliation to the Fabaceae family ("Fabaceae" versus "no Fabaceae"). Fabaceae species are of special interest, because they are the only N-fixing vascular plants found on the catchment.…”
Section: Vegetationmentioning
confidence: 99%
“…When compared to non-glaciated catchments, the exported amount of OC of glacier ecosystems is typically low [5][6][7][8]. Exports support heterotrophic metabolism in proglacial streams, as the bioavailability of glacier-derived OC is noticeably higher (BDOC, 59 ± 20%; [3]) than those from headwaters in forested catchments (25 ± 5%; [8]) or in structured natural catchments, including forests, agricultural soils, or wetlands (mean 25%; [9]). Moreover, compared to temperate catchments, there are relatively less terrigenous OC inputs from the riparian zone or organic soils in glaciated catchments [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These temperate glaciers have been shown to be particularly sensitive to climatic fluctuations on an annual to decadal scale [26]. Since the mid-1990's, Icelandic glaciers have shown an average annual mass loss of 9.5 ± 1.5 Gt•yr −1 , resulting in a total loss of 84 km 3 from the icecap volume [9,27,28]. Due to the altitude differences and the geographical position of the glaciers within Iceland, at the border between Arctic and temperate seas, and the cold air masses of the Arctic and warm air masses of lower latitudes, Icelandic glaciers show varying mass balances depending on their position and aspect [20].…”
Section: Introductionmentioning
confidence: 99%